THE NEUTRALIZATION OF TOXIC GAS CLOUDS IN THE ATMOSPHERE - Biliaiev, M. M.; Lysniak, V. M. (Science and Transport Progress, 2009)
The 3D CFD model to simulate the pollutant transfer and the process of neutralization of toxic gas after accidents was developed. The model is based on the transport gradient model. The results of numerical experiments are presented.